Aplikasi Energi Terbarukan Melalui Pengukuran Potensi Angin dengan Metode Analisis Weibull pada Pantai Puger Jember - Parmaputra Widiyanto; Miftachul Arif; Triwahju Hardianto (Fakultas Teknik, Universitas Jember, 2015)
AbstractThe territory area of south sea Jember Regency gets potential to bebuilt a PLTA because it has great wind potential of energy whichsupports it. One of the parameters to know the wind characteristicsis by using weibull analysis. Wind speed characteristic on thePuger beach has range among 1,3-15,0 m/s, so it can be taken upabout the distribution-probability characteristic of it by making aWeibull characteristic curve by using a k-form(k) parameter is3.068; and for scale parameter (c) is 7.807. From this result, weconclude that the wind speed which can be used at the range of 3,5m/s-10.5 m/s reaches 91.11 %, so it still has enough potential to bebuilt a PLTA by a turbine from small to moderate range in size.Meanwhile, by looking from its power potential, by the averagewind speed of 6.1 m/s, it has power potential of 3025 watt and theabsorbed power by the turbine reaches 1758 watt. This value wouldbe useful enough if the number of used turbine getting bigger.Keywords—Weibull Analiys, Puger Beach, Power potential